PIP-II Injector Test cryogenic transfer line. Issue 1 (March 2020) - Wang, Renzhuo; Hansen, Benjamin; Hurd, Joseph; Martinez, Alexander; Klebaner, Arkadiy
Abstract: PIP-II Injector Test will test a nearly full-scale front end of PIP-II accelerator. The cryogenic transfer line will provide 2 K, 5 K and 40 K refrigeration for Half Wave Resonator and Single Spoke Resonator cryomodules. This paper will focus on design, installation and operation plan of the cryogenic transfer line.